Sensing layer combination of vertically aligned ZnO nanorods and graphene oxide for ultrahigh sensitivity IDE capacitive humidity sensor. Issue 6 (7th April 2020) - Pongampai, Satana; Pengpad, Puttapon; Meananeatra, Rattanawan; Chaisriratanakul, Woraphan; Poyai, Amporn; Horprathum, Mati; Chananonnawathorn, Chanunthorn; Titiroongruang, Wisut; Muanghlua, Rangson
Abstract : An interdigitated electrode (IDE) capacitive humidity sensor fabricated on a silicon substrate was used to investigate sensing materials, which proved to be an ultrahigh‐sensitivity humidity sensor. A sensing layer combination (SLC) between vertically aligned ZnO nanorods and optimal graphene oxide (GO) was prepared on the device and was tested as a humidity sensor. X‐ray diffractometry (XRD) exhibited crystallized wurtzite structure of ZnO nanorods and transmission electron microscope (TEM) shown perfectly indexed hexagonal wurtzite ZnO structure dots position correspondence. A scanning electron microscope (SEM) was used to analyze ZnO nanorods/GO morphologies. Furthermore, Raman spectroscopy and X‐ray photoelectron spectroscopy (XPS) clearly exhibited GO presence and hydrophilic functional groups (carboxyl, epoxy, and hydroxyl), respectively. The SLC prominently demonstrated ultrahigh sensitivity (up to 196.95% or 1.97 times from commercial sensor; HS1101, Humirel) and linear responses behavior with 0.96 for coefficient of determination. The device sensitivity obviously improved as steps of 40, 50, 60, 70, 80, and 90% RH at values of 1.09, 1.41, 1.51, 1.65, 1.80, and 1.91 times, respectively. The device also exhibited fast response (25 s) and short recovery times (17 s). Its hysteresis (6.58%) manifestly improved to 1.84 times. Moreover, repeatability and long‐term ability of the device demonstrated high accuracy (range ±0.37pF) and durability. © 2020 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.